Ethanol production from local biomass (rice husk) using yeast and zymmomonas mobilis, its optimization using TiO2 and characterization using HPLC and FTIR analysis - Amna Meer (NUST201361515MCES64113); Dr. Ehsan Ali (USPCAS-E, NUST, Islamabad, 2015)
TH-30
Keywords: MS-ESE Thesis MS Thesis